2018
DOI: 10.5194/acp-18-10333-2018
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting interannual atmospheric CO<sub>2</sub> variabilities and their terrestrial mechanisms for two types of El Niños

Abstract: Abstract. El Niño has two different flavors, eastern Pacific (EP) and central Pacific (CP) El Niños, with different global teleconnections. However, their different impacts on the interannual carbon cycle variability remain unclear. Here we compared the behaviors of interannual atmospheric CO 2 variability and analyzed their terrestrial mechanisms during these two types of El Niños, based on the Mauna Loa (MLO) CO 2 growth rate (CGR) and the Dynamic Global Vegetation Model's (DGVM) historical simulations. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 55 publications
(96 reference statements)
7
29
0
Order By: Relevance
“…Thus, the specifically-applied spatial averaging procedure to remap the finer RADOLAN grid data to the coarser GPM grid utilizes the first order conservative remapping scheme from Jones [64], comprised in the Climate Data Operators software (CDO), which applies the SCRIP algorithm (Spherical Coordinate Remapping and Interpolation Package) [65,66]. This technique is widely applied in other studies dealing with precipitation data [67][68][69]. The area-averaged precipitation quantityF k at the destination grid is calculated as follows:…”
Section: Preprocessing Of Datasetsmentioning
confidence: 99%
“…Thus, the specifically-applied spatial averaging procedure to remap the finer RADOLAN grid data to the coarser GPM grid utilizes the first order conservative remapping scheme from Jones [64], comprised in the Climate Data Operators software (CDO), which applies the SCRIP algorithm (Spherical Coordinate Remapping and Interpolation Package) [65,66]. This technique is widely applied in other studies dealing with precipitation data [67][68][69]. The area-averaged precipitation quantityF k at the destination grid is calculated as follows:…”
Section: Preprocessing Of Datasetsmentioning
confidence: 99%
“…Yeh et al, 2009). Despite recent research finding that the expression of El Niño is important at interannual timescales (Wang et al, 2018;Chylek et al, 2018;Pan et al, 2018), it is not known how and where the recent trend towards more CP El Niño events would impact the terrestrial carbon cycle.…”
Section: Introductionmentioning
confidence: 98%
“…Scheiter and Higgins, 2009;Whitley et al, 2017). Recent studies have found that, depending on the expression of El Niño, different time lags, amplitudes and duration in the carbon cycle anomalies occur (Wang et al, 2018;Chylek et al, 2018). Wang et al (2018) and Chylek et al (2018) link the effects of different expressions of El Niño on the terrestrial carbon cycle to variability at interannual timescales, but the impact on longer timescales is not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patterns of precipitation are correspondingly different. Depending on the types of ENSO events, their impacts on terrestrial carbon cycle can be quite different or even contrast (Wang et al ., ; ). In response to a specific ENSO event, precipitation over the three tropical continents can have different anomalies (Malhi and Wright, ; Liu et al ., ).…”
Section: Introductionmentioning
confidence: 99%